2019
DOI: 10.1021/acsinfecdis.9b00228
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Robustness of Inhibitors of Tuberculosis Aminoglycoside Resistance Enzyme Eis by Mutagenesis

Abstract: Each year, millions of people worldwide contract tuberculosis (TB), the deadliest infection. The spread of infections with drug-resistant strains of Mycobacterium tuberculosis (Mtb) that are refractory to treatment poses a major global challenge. A major cause of resistance to antitubercular drugs of last resort, aminoglycosides, is overexpression of the Eis (enhanced intracellular survival) enzyme of Mtb, which inactivates aminoglycosides by acetylating them. We showed previously that this inactivation of ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Unfortunately, such a successful alternative has not yet been fully developed for aminoglycosides. Despite significant efforts, no formulations that combine an aminoglycoside and an inhibitor of the resistance have been approved for human use [4,38]. Although there are many mechanisms and variations by which bacteria resist aminoglycosides, the presence of AAC( 6)-Ib in the majority of Gram-negative amikacin-resistant clinical strains implies that the search to find inhibitors that permit their use in a significant number of infections may not be as insurmountable as it seems [4,8,39].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, such a successful alternative has not yet been fully developed for aminoglycosides. Despite significant efforts, no formulations that combine an aminoglycoside and an inhibitor of the resistance have been approved for human use [4,38]. Although there are many mechanisms and variations by which bacteria resist aminoglycosides, the presence of AAC( 6)-Ib in the majority of Gram-negative amikacin-resistant clinical strains implies that the search to find inhibitors that permit their use in a significant number of infections may not be as insurmountable as it seems [4,8,39].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, such a successful alternative has not yet been 15 fully developed for aminoglycosides. Despite significant efforts, no formulations that 16 combine an aminoglycoside and an inhibitor of the resistance have been approved for 17 human use [4,35]. Although there are many mechanisms and variations by which bacteria 18 resist aminoglycosides, the presence of AAC(6′)-Ib in the majority of Gram-negative 19 amikacin-resistant clinical strains implies that the search to find inhibitors that permit 20 their use in a significant number of infections may not be as insurmountable as it seems 21 [4,8,36].…”
Section: Potentiationmentioning
confidence: 99%
“…In a previous manuscript, Green and co-authors [38] used three compounds (89-91, Figure 40) belonging to different structural families to demonstrate how Eis mutations can influence the potency of the inhibitors. Compound 89 belongs to the same family of analogue 87 [36] and its crystal structure showed the same interactions illustrated above for 87 and 88.…”
Section: Enhanced Intracellular Survival (Eis) Transferasementioning
confidence: 99%
“…An NMRbased activity assay showed that the activity of MenD at a concentration of 5 μM was Starting from this information, seven residues (Asp26, Trp36, Arg37, Leu63, Met65, Ser83, and Phe84) not directly involved in the acetyl transfer function of Eis, but observed to interact with the inhibitors, were mutated into alanine residues to determine the effects on aminoglycoside acetylation and on inhibitor binding. The results showed that mutations in only three amino acids (Asp26Ala, Trp36Ala, and Phe84Ala) rendered all inhibitors inactive, suggesting that the future design of inhibitors should not depend on interactions with these residues [38].…”
Section: -Succinyl-5-enolpyruvyl-6-hydroxy-3-cyclohexadiene-1-carboxylate Synthase (Mend)mentioning
confidence: 99%
See 1 more Smart Citation